Efficiency of preliminary cooling of berries - Lomeiko, Oleksandr; Ломейко, Олександр Петрович; Ломейко, Александр Петрович; Kulinchenko, Vitalі (My University, 2016)
The previous cooling of berries is a process of rapid drop in their temperature from initial (after harvesting) to necessary in the adjusted for this purpose hard wares at subsequent technological operations. Than quick to reduce the temperature of berry, the more protracted will be a period of storage of them in a refrigerator. As a result of changes the losses of bacchante products are abbreviated from over ripening, de growth, physiology diseases and spoilage, and also the food value of berry is saved. The terms of refrigeration storage of products are thus increased: to the vine - on 1-1,5 month, drupaceous - on 0,5 month, berries (depending on a kind and sort) - on one and more than weeks. Advantage of the previous cooling is that at a load in the chambers of frappe backdate products the nonpermanent filling of all of volume of baggage and creation of the most optimum and stable temperature condition room is possible from the initial stages of storage. At the daily receipt of parties of undrape berry in a volume not more than 10% from the capacity of baggage room the thermal loading on the compressor equipment of refrigerator is at high level during all of period of load of berry (10 days) and proceeds yet during 3 days after him. At the same time at storage of preliminary frappe berry possibly already on the second time of lowering of the thermal loading to the parameters of the stationary mode and support of it during all of period of book-mark of products on storage. Most stationary depositories intended for the protracted storage of products. Mainly it is depositories, placed in a direct closeness from gardens, berry patches, plantations and attendant at once a few peasant and farmer economies. Cooling’s of fruit, berries and vine more frequent conduct storage of stationary refrigerators in chambers. A capacity of loft-rooms is from 500 to 10000 ton. Together with chambers for refrigeration storage they include chambers for the previous cooling, which provide cooling of products to the temperature of storage for 20 hours at the volume of receipt of it to a 10% capacity of chambers. By us setting which consists of the module was created: chambers of maintenances, refrigeration machine and stand mounted for it are from CMI for measuring of basic indexes of process. The followings parameters changed during researches: time, т works of setting, temperature of tnов and charges of environment, Qnов, that cools, on a serve in the cooled volume. The direct and no right measuring of regime parameters were conducted. The feature of method of improvement of quality of storage by the conduct of operation of blowing out of frappe air a ventilator through the layer of berries is that ventilators can be disposed as with gen a stack with products so directly in intervals between stacks. Thus small suction ventilators create streams into stacks with products. The combined method of cooling of air through all of layer of berries retimed the best results, that brings to reduction of time cooling over of berries and increase of shelf-lives products on 15-20%. As a result of experiments shelf-life strawberry garden made 10 days, currant black - 20 days, currant red - 30 days. Thus a food value of berries was high.
Ефективність попереднього охолодження ягід
Keywords: cooling; garden-stuffs; berries; emperature; refrigerator; depository